A study of relationship between parenting styles and self-esteem : self-esteem's indicator-parenting styles - Lee, Yen Chiew (2011)
Parenting style is an important topic to discuss nowadays. Previous research has reported a relation between parenting styles and self-esteem across different ethnic groups as well as various countries. This study examines the association and relationship between different parenting styles and self-esteem on Universiti Tunku Abdul Rahman (UTAR). A sample of 100 UTAR students completed questionnaires that include Parental Authority Questionnaire (PAQ) and Rosenberg Self-esteem Scale (RSE). Result displayed that authoritative parenting style is the predominant parenting style and there was significant correlation between different parenting styles and self-esteem. Significant association was found between authoritative and authoritarian parenting style on levels on self-esteem. Greater numbers of students from authoritative families have high level of self-esteem than authoritarian families. Limitations have been stated and recommendations are provided in the discussion part. As a conclusion, present study stated that parents’ roles and their parenting styles play critical role in influencing self-esteem of children.